Competing Objectives in the Reorganization of Maine State Government - Palmer, Kenneth (Maine Policy Review, 1993)
The budget difficulties faced by Maine and by most other states have prompted a national search for better ways to deliver government services. In Maine, a conference entitled "Rethinking Maine Government" was held at the University of Maine on January 5-6, 1993 under the auspices of the Margaret Chase Smith Center for Public Policy. MPR has selected three of the presentations at that conference for this issue. Kenneth Palmer in this article provides a historical view on previous efforts to reorganize Maine government.